Computational fluid dynamics study of PEM fuel cell performance for isothermal and non-uniform temperature boundary conditions. (19th October 2016) - Penga, Željko; Tolj, Ivan; Barbir, Frano
Abstract: Computational fluid dynamics (CFD) study of segmented proton exchange membrane fuel cell (PEMFC) performance has been carried out, based on experimental setup and operating parameters from previous studies. Two different temperature boundary conditions were considered – isothermal and, a novel, non-uniform temperature profile calculated from Mollier h-ω chart. Implementation of non-uniform terminal temperature boundary conditions resulted in close to 100% relative humidity along the cathode channel, resulting in improvement of PEMFC performance without the need for external humidification. Model polarization curve and relative humidity distribution along the cathode channel length are in good agreement with experimental results. It was found that different current collector materials, i.e., their thermal conductivity have major influence on temperature, thus on relative humidity distributions along reactant gas channels. The membrane thickness affects the net water transport across the membrane, thus also has influence on temperature and relative humidity distribution along the reactant gas channels. Highlights: Concept of variable temperature field along the cathode channel has been studied. CFD model of a segmented cell has been calibrated and verified by experimental results. Close to 100% relative humidity along the cathode channel was achieved without external humidification. Isothermal and non-uniform boundary conditions have been compared.